2015
DOI: 10.1007/s11948-015-9714-5
|View full text |Cite
|
Sign up to set email alerts
|

Plagiarism Allegations Account for Most Retractions in Major Latin American/Caribbean Databases

Abstract: This study focuses on retraction notices from two major Latin American/Caribbean indexing databases: SciELO and LILACS. SciELO includes open scientific journals published mostly in Latin America/the Caribbean, from which 10 % are also indexed by Thomson Reuters Web of Knowledge Journal of Citation Reports (JCR). LILACS has a similar geographical coverage and includes dissertations and conference/symposia proceedings, but it is limited to publications in the health sciences. A search for retraction notices was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 24 publications
1
20
1
4
Order By: Relevance
“…In the same vein, other studies have found that errors in reported research are a global issue [5, 13]. However, a survey of the general biomedical literature showed that the origin of the authors was related to the reason for retraction: the rates of retractions due to fraud was higher in the United States, German, Japan and China, whilst plagiarism was more common reason in India and China [5].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In the same vein, other studies have found that errors in reported research are a global issue [5, 13]. However, a survey of the general biomedical literature showed that the origin of the authors was related to the reason for retraction: the rates of retractions due to fraud was higher in the United States, German, Japan and China, whilst plagiarism was more common reason in India and China [5].…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies investigating characteristics of retracted papers focused on general medicine [12, 13], mental disorders [14], pharmacology [15], radiology [16], and biomedical literature [17], as well as specific topics such as retraction differences across countries [18], scholarly literature in PubMed [10, 19, 20], and noncompliance with human rights in retracted medical papers [11]. However, specific studies about trends and factors associated with retractions in dentistry are still lacking [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examining the motivation and context in such cases is critical for preventing misconduct in the future. Although the number of retractions due to plagiarism is not high (81 [1.6%] of documents in Scopus), the high prevalence of such cases in the medical literature, primarily affecting rapidly developing disciplines and emerging scientific powers, is worrying (67). …”
Section: Lessons Learned From Retractionsmentioning
confidence: 99%
“…Discussing plagiarism in Latin America is an important issue, given the dramatic growth of research activities in the region in the last two decades (Van Noorden 2014; Catanzaro et al 2014). In particular, sporadic reports have highlighted the occurrence of plagiarism in research conducted in Latin America (Vasconcelos et al 2009; Alfaro-Tolosa et al 2013), and the reaction of scientific journals (Alfaro-Tolosa et al 2013; Almeida et al 2015). In addition, Latin American countries share many cultural features, arising from their common colonial history, that may affect how plagiarism and cheating are perceived (Martin 2012; Salter and Guffey 2001), including collectivism, high uncertainty avoidance, high power distance, high indulgence, and a short-term orientation (Hofstede 2011).…”
Section: Introductionmentioning
confidence: 99%